2012
DOI: 10.1007/s00425-012-1796-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a tuberous root-specific promoter from cassava (Manihot esculenta Crantz)

Abstract: In order to obtain a tuberous root-specific promoter to be used in the transformation of cassava, a 1,728 bp sequence containing the cassava granule-bound starch synthase (GBSSI) promoter was isolated. The sequence proved to contain light- and sugar-responsive cis elements. Part of this sequence (1,167 bp) was cloned into binary vectors to drive expression of the firefly luciferase gene. Cassava cultivar Adira 4 was transformed with this construct or a control construct in which the luciferase gene was cloned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…These differences are probably because we were using Adira genotypes from BALITKABI, Indonesia instead of AM560-2 genotypes developed by CIAT, Columbia [45]. The same results were reported by other cassava researcher when the sequences were isolated from different genetic background [60]. Interestingly, MeEF1A3 promoter had 90% similarity to corresponding sequence at the scaffold 03015 from database.…”
Section: Discussionsupporting
confidence: 57%
“…These differences are probably because we were using Adira genotypes from BALITKABI, Indonesia instead of AM560-2 genotypes developed by CIAT, Columbia [45]. The same results were reported by other cassava researcher when the sequences were isolated from different genetic background [60]. Interestingly, MeEF1A3 promoter had 90% similarity to corresponding sequence at the scaffold 03015 from database.…”
Section: Discussionsupporting
confidence: 57%
“…Recently, tissue-specific promoters have become the focus of plant genetic engineering. Researchers have isolated, cloned, and studied many tissue-specific promoters from different plants (Guo et al, 2010; Koehorst-van Putten et al, 2012; Chen et al, 2013; Zhu et al, 2014; Liu et al, 2015; Xue et al, 2018). The third type of promoter, the inducible promoter, is activated by abiotic or biotic stresses or hormone induction.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the GBSSI promoter showed very low expression in the first three organs, but very high expression in the latter one. These findings indicated that the cassava GBSSI promoter is the best candidate to achieve tuberous root-specific expression in cassava (Koehorst-van Putten et al, 2012a). Recent research conducted by team of Chinese Academy of Sciences (CAS) successfully produced high amylose transgenic cassava by down regulating BE genes, which are responsible for amylopectin biosynthesis (Zhou et al, 2020).…”
Section: Introductionmentioning
confidence: 96%